Differential impact of Toll-like receptor signaling on distinct B cell subpopulations - Meyer-Bahlburg, Almut (2012)
B cells exhibit a range of functional responses following TLR engagement including immunoglobulin and cytokine production, proliferation, antigen presentation and migration. However, B cell intrinsic TLR responses appear to be precisely programmed based upon the developmental stage of the cell. B cell subpopulations classified as innate immune cells including marginal zone and B-1 B cells exhibit robust responses to TLR stimulation. In contrast, activation of other B cell subsets is constrained via a variety of developmentally regulated events. In this review we provide an overview of TLR responses in murine and human B cells and specifically highlight patterns of TLR expression and developmentally regulated functional responses.